PEMODELAN JUMLAH PENUMPANG KAPAL DOMESTIK DI PELABUHAN TANJUNG PERAK MENGGUNAKAN MODEL VARIASI KALENDER SEASONAL ARIMAX - Ninda Permata Riau; Ferra Yanuar; Dodi Devianto (Jurnal Lebesgue)
Indonesia is the largest archipelagic country in the world, heavily reliant on maritime transportation, with Tanjung Perak Port being the second busiest port, playing a strategic role in East Java's economy. Analysis shows that fluctuations in the number of ship passengers at Tanjung Perak Port are influenced by seasonal patterns and calendar variations, such as spikes in passenger numbers during the Eid Al-Fitr holiday. To model these fluctuations, the SARIMAX (Seasonal ARIMA with Exogenous Variables) model is used, which accounts for both seasonal factors and exogenous variables. Results of this research show a significant relationship between the number of ship passengers and a dummy variable representing the month before and during Eid al-Fitr. The SARIMAX model used in this analysis confirms that the period leading up to and during the Eid al-Fitr celebration contributes significantly to fluctuations in passenger numbers.